2018
DOI: 10.1038/s41598-018-34892-9
|View full text |Cite
|
Sign up to set email alerts
|

A versatile method for the UVA-induced cross-linking of acetophenone- or benzophenone-functionalized DNA

Abstract: Bioconjugation, biosensing, bioimaging, bionanomaterials, etc., are only a few examples of application of functionalized DNA. Since base-modified nucleic acids contribute not only to a broad range of biotechnological fields but also to the understanding of various cellular processes, it is crucial to design novel modifications with unique properties. Here, we demonstrate the utilization of N4-cytidine modified oligonucleotides, which contain reactive acetophenone (AP) or benzophenone (BP) groups, for the UV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Furthermore, N 4 modification could complement the already known photocaging strategy and become a great tool for the regulation of gene expression. Considering the crosslinking or photo‐immobilisation possibilities of AcBz or BzBz functional group containing DNA demonstrated earlier, the demodification step would enable the separation of modified DNA and the covalently linked substrate to delve more deeply into the bioconjugation mechanism. Moreover, given that, in some cases, the modified ONs can be incompatible with downstream amplification procedures (e.g., PCR or reverse transcription), there might be a necessity to remove modifications, while leaving the whole nucleic acid molecule unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, N 4 modification could complement the already known photocaging strategy and become a great tool for the regulation of gene expression. Considering the crosslinking or photo‐immobilisation possibilities of AcBz or BzBz functional group containing DNA demonstrated earlier, the demodification step would enable the separation of modified DNA and the covalently linked substrate to delve more deeply into the bioconjugation mechanism. Moreover, given that, in some cases, the modified ONs can be incompatible with downstream amplification procedures (e.g., PCR or reverse transcription), there might be a necessity to remove modifications, while leaving the whole nucleic acid molecule unaffected.…”
Section: Resultsmentioning
confidence: 99%
“…84 For example, terminal deoxynucleotidyl transferase enzyme could be crosslinked to 3 0 -tails of DNA containing benzophenones and acetophenones on N 4 -dC's using 365 nm light (Fig. 8) 87 Reaction characteristics. UV irradiation (365 nm) of benzophenones generates C-O biradical through n-p* transition, which can lead either to photocrosslinking or its reversal, photocleavage.…”
Section: Benzophenone and Acetophenonementioning
confidence: 99%
“…86 On the other hand, benzophenone-and acetophenone-modications on N 4 -dC could generate protein-DNA crosslinks with the bound terminal deoxynucleotidyl transferases using 365 nm light. 87…”
Section: Benzophenone and Acetophenonementioning
confidence: 99%
“…This product was proposed based on NMR and UHPLC-MS/MS analysis of the byproducts following irradiation. In a dual crosslinking and immobilization approach, Jakubovska et al [72] functionalized N 4 -cytidines with BP and demonstrated the dual usefulness of the installed BP. Through BP-mediated crosslinking, they successfully (1) immobilized the modified oligonucleotides to polymeric solid supports and (2) covalently labelled interacting proteins of the oligonucleotide.…”
Section: Other Applications Incorporating Bp Probesmentioning
confidence: 99%